2021
DOI: 10.1088/1361-6463/abd355
|View full text |Cite
|
Sign up to set email alerts
|

2D numerical modeling for plasma-assisted CO2 pooling in supersonic nozzles: importance of a proper nozzle contour design

Abstract: Plasma assisted CO 2 dissociation has recently been the topic of many studies. The production of chemical fuels from environmentally unfriendly CO 2 through supersonic nozzles is one of the most prominent approaches under investigation. However, the experiments show that the theoretical conversion rates are far away from being achieved. In this study, two-dimensional fully coupled cases are investigated. This brings insights about how the CO 2 dissociation can be improved; mainly by a correct design of nozzles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 20 publications
(67 reference statements)
0
24
0
1
Order By: Relevance
“…F I G U R E 1 Sketches of two different types of nozzle, in both cases, showing the separation of the subsonic and supersonic zone by a throat where the Mach number equals M* = 1; the left structure is based on a cosine form as used in studies Peerenboom et al [13] and Khaji et al [14] ; the right is a design based on a MOC design. [16] The dashed line at the bottom in 2D planar and axisymmetry nozzles refer to, respectively, a symmetry plane and a line of rotation Apart from the quantities, ρ p , , and u introduced above, we find the mass-related energy density E (in J/kg) and the power density ∕ ω ˙(W m ) H 3 associated with the change in chemical composition. The former can be expressed via:…”
Section: Flow; General Aspectsmentioning
confidence: 77%
See 4 more Smart Citations
“…F I G U R E 1 Sketches of two different types of nozzle, in both cases, showing the separation of the subsonic and supersonic zone by a throat where the Mach number equals M* = 1; the left structure is based on a cosine form as used in studies Peerenboom et al [13] and Khaji et al [14] ; the right is a design based on a MOC design. [16] The dashed line at the bottom in 2D planar and axisymmetry nozzles refer to, respectively, a symmetry plane and a line of rotation Apart from the quantities, ρ p , , and u introduced above, we find the mass-related energy density E (in J/kg) and the power density ∕ ω ˙(W m ) H 3 associated with the change in chemical composition. The former can be expressed via:…”
Section: Flow; General Aspectsmentioning
confidence: 77%
“…The models presented in Peerenboom et al [13] and Khaji et al [14] are based on one-dimensional (1D) configurations. However, it was found in Khaji et al [16] that a 2D description of the flow in the cosine-like configuration used in Peerenboom et al and Khaji et al [13,14] reveals the presence of shock waves, a phenomenon that was also found in other CO 2 valorization studies. [5,17] That shocks must be avoided is evident if we realize that they generate heat, that this facilitates VT transitions and thus frustrates the push-up of the VDF-tail.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations